Creation and application of knowledge base of specialists' competence profiles in an organization; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 2 - Tuzovskiy A. F. Anatoliy Fedorovich (Control, computer engineering and information, 2007)
Заглавие с титульного листа